Desain dan Implementasi Bimbingan Online dan Monitoring Tugas Akhir Mahasiswa di Universitas Stella Maris Sumba - Herman Huki Ratu; Yulius Nahak Tetik (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The Final Project is an official work that consists of a thesis or an artwork, which is the result of research or scientific creation by students, conducted through a series of steps and procedures in accordance with the Final Project (TA) guidelines set by each faculty. One strategy to encourage students to complete their studies as quickly as possible is to require students who are working on their Final Project (TA) to attend campus at least once a week to report on their progress while bringing their Final Project guidance card. Interviews are conducted with students to find a supervising lecturer, students hold proposal guidance, after which the proposal is validated, students then register for the proposal seminar, students conduct the proposal seminar, a decree (SK) is issued, students continue with Final Project guidance, the documentation of the Final Project is validated, students register for the results seminar and final defense, as well as students undergoing plagiarism checks. This is due to the lack of application platforms that can monitor students' completion of their final projects online. Therefore, research on an information system application to supervise students' final projects is very much needed.